A rare cause of obstructive jaundice: Fasciola hepatica mimicking cholangiocarcinoma - Orçun YALAV; Özgür YAĞMUR; Abdullah ÜLKÜ; Atılgan Tolga AKCAM; Hüsnü SÖNMEZ (Turkish Journal of Gastroenterology, 2019)
-